The Biological Basis for Mind Body Interactions - Science and Practice of Mind/Body Interactions (Conference) (1998 : Sedona, Ariz.); Mayer, E. A.; Saper, C. B. (Clifford B.); ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2000)
The current volume focuses on several key aspects of mind/brain/body interactions in health and disease, including specific examples of interactions between body and brain, mechanisms underlying the response of the system to stressors, the role of early life events in permanently biasing the responsiveness of the system and practical implications of mind body interactions in human disease.
Part I: Introduction -- Part II: Relationship between mind, brain and emotions -- Part III: The neurobiology of the stress response -- Part IV: Early life experiences and the developing brain -- Part V: Influences of the internal environment on the brain -- Part VI: Influences of the body on the brain -- Part VII: The influence of brain and mind on the body -- Part VIII: Practical use of mind-body interactions in medicine.
Text in English.
"The symposium on the 'Science and Practice of Mind/Body Interactions' was organized by Emeran A. Mayer ... and Clifford Saper ... held March 15-18, 1998 in Sedona, Arizona"--Acknowledgements.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Brain -- Physiology -- Congresses; Mind and body -- Congresses; Mind and body therapies -- Congresses; Stress (Physiology) -- Congresses; Psychobiologie; Esprit et corps; Thérapies corporelles; Stress; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Brain -- Physiology; Mind and body; Mind and body therapies; Stress (Physiology); Hersenfuncties; Psychobiologie; Brain -- physiology; Mind-Body Relations, Metaphysical; Psychophysiology; Electronic books